A new approach to determine tumor-to-blood 10B concentration ratios from the clinical outcome of a BNCT treatment - González, Sara Josefina (2004)
A new approach to determine the tumor-to-blood 10B concentration ratio in boron neutron capture therapy (BNCT) is introduced. It is a statistical method, which uses maximum likelihood estimation on the clinical outcome of a BNCT treatment. Its performance is shown in a clinical case of cutaneous multiple nodular melanomas. The calculations involve a detailed dosimetry analysis, the determination of tumor control probabilities for the different nodules, the maximum likelihood estimation itself, and a parametric bootstrap to obtain confidence intervals for the tumor-to-blood ratio. The obtained ratio is 3.05±0.46 with a 95%-confidence interval. These results are consistent with those found in literature. Moreover, a single patient with multiple nodules proves enough to get statistically relevant results. The proposed method does not involve surgery and can be performed after a BNCT treatment without being invasive for the patient.